When the Devil Plays the Guitar and the Preacher Prays for Mercy: An Exploration of Two Filmic Portrayals of the Occult and Satanism in Rock Music - Treiber, Fritz (Journal for religion, film and media, 2023)
"The Devil is a catchy lyric." This quote from the movie American Satan (Ash Avildsen, US 2017), when Mr. Capricorn (the devil) promises international success to a young heavy-metal band in Los Angeles and its singer, Johnny Faust. The pact must be sealed with a human sacrifice. Linking rock or heavy metal with the devil or demonic powers is a theme that has been used repeatedly in music and film. In this article, two films from independent productions are analyzed to study how the devil reaches people through rock music and ultimately influences their actions. In addition, the temporal context and the events that affected the content of the screenplays are discussed.